Rediscovery and systematics of Rhinophis fergusonianus Boulenger, 1896 (Serpentes: Uropeltidae) from India’s Western Ghats - Gower, David J.; Narayanan, Surya; Deepak, V.; Y., Muhammed Anvar; Das, Sandeep (Zootaxa, 2023)
The shieldtail snake Rhinophis fergusonianus Boulenger, 1896 was previously known only from the holotype specimen collected approximately 130 years ago from an imprecise Indian locality (Cardamom Hills). We report the rediscovery of this species from four localities, from low-elevation hills on both sides of the Palghat Gap in the southern part of the Western Ghats of peninsular India. We document new specimens of R. fergusonianus and provide a reassessment of the systematics of the species based on external morphology and DNA-sequence data. We also provide a revised key to the identification of Indian species of Rhinophis.